2019
DOI: 10.1093/mnras/stz1556
|View full text |Cite
|
Sign up to set email alerts
|

Polarization and brightness temperature observations of Venus with the GMRT

Abstract: Venus was observed at frequencies of 1297.67 MHz (23 cm), 607.67 MHz (49 cm) and 233.67 MHz (1.28 m) with the Giant Metrewave Radio Telescope (GMRT) during the period of 25th July and 6th September 2015 when it was close to its inferior conjunction. Values of the brightness temperature (T b ) of Venus from these observations were derived as 622±43 K, 554±38 K for 1297.67 and 607.67 MHz frequencies, respectively, are in agreement with the previous observations. The attempt to derive the T b at 233.67 MHz affirm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…In order to minimize the observation time, we chose to observe 3C 48, which is unpolarized at these frequencies (Perley & Butler 2013;Farnes et al 2014), allowing us to determine the leakage terms. For calibrating the polarization position angle, we used 3C 286 following Mohan et al (2019). However, we obtained a polarization fraction of ∼3.5% for 3C 286 at 650 MHz, which agrees with the value of 2.7% at 610 MHz by Farnes (2012) but is in tension with the value of 7.6% at 607 MHz given by Mohan et al (2019).…”
Section: Polarizationsupporting
confidence: 74%
“…In order to minimize the observation time, we chose to observe 3C 48, which is unpolarized at these frequencies (Perley & Butler 2013;Farnes et al 2014), allowing us to determine the leakage terms. For calibrating the polarization position angle, we used 3C 286 following Mohan et al (2019). However, we obtained a polarization fraction of ∼3.5% for 3C 286 at 650 MHz, which agrees with the value of 2.7% at 610 MHz by Farnes (2012) but is in tension with the value of 7.6% at 607 MHz given by Mohan et al (2019).…”
Section: Polarizationsupporting
confidence: 74%
“…(2001) are given in filled black circle, and the GMRT observations reported by Mohan et al. (2017, 2019) are given in filled red circles. The vertical lines in the measurements indicate the standard deviation in the observed T b .…”
Section: Radiative Transfer Simulation For Surface Thermal Emissionmentioning
confidence: 99%
“…(2001) also arrived at similar results. Figure 1 shows the comparison of the simulated T b with various radiometric observations, including the VLA observations (Butler et al., 2001) and GMRT observations (Mohan et al., 2017, 2019). The RT simulations (thick black line in Figure 1) with a single layer of infinite depth with uniform dielectric constant fails to capture the observed decrease in T b with increase in wavelength.…”
Section: Radiative Transfer Simulation For Surface Thermal Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Saxena et al (2018) have discovered the most distant radio galaxy identified to date at a redshift of z = 5.72. Mohan et al (2019) described polarizations and brightness temperature observations of Venus, placing constraints on its emission mechanism. Using the uGMRT, neutral hydrogen, Hi, has been detected at a redshift of 0.37 by stacking 445 16…”
Section: The Giant Metrewave Radio Telescopementioning
confidence: 99%